Temporal trends of cervical cancer demographics: a CDC WONDER database study - Folino, Grace; Zent, Isabella; Eason, Lillian; Murugan, Vikram; Billion, Taylor; Abdul Jabbar, Ali Bin; Mirza, Mohsin; Tauseef, Abubakar (Frontiers in Oncology, 2025)
IntroductionDespite advancements in cervical cancer screening and HPV vaccines, demographic disparities perpetuate the burden of cervical cancer. The aim of this study is to utilize the most up-to-date CDC WONDER data of cervical cancer mortality to provide a comprehensive temporal analysis of demographic variables and account for patients missed in other database studies. In doing so, temporal trends found in this study may be used to guide future efforts and studies to understand nuanced barriers to cervical cancer screening and prevention.MethodsWith CDC WONDER Data, cervical cancer-related mortality was assessed in the U.S. from 1999 to 2023. Using age-adjusted mortality rates (AAMR), temporal trends were analyzed using the Joinpoint Regression Program for women 25 years and older across race, census regions, urban/rural residence, and states. Annual percentage change (APC) and average annual percentage change (AAPC) were calculated with 95% confidence intervals.ResultsCervical cancer-related mortality declined over the study period with an AAPC of –1.043*. Between 2015 and 2023, there was a concerning positive change in AAMR [APC of 0.1272 (95% CI –0.3393 to 1.7502)], though not statistically significant. Black or African American patients experienced the highest AAMR across races but maintained a decrease in mortality rate over the study period [AAPC of -2.670* (95% CI -2.931 to -2.356)]. Region and race analysis demonstrated Black or African American patients in the Northeast held the largest decline in AAMR [AAPC of –3.218* (95% CI –3.708 to –2.390)], while Hispanic or Latino and Black or African American patients in the South closely followed AAPC of –1.347* (–1.898 to –0.824) and –2.656* (95% CI –2.939 to -2.350), respectively]. Rural areas (NonCore and Micropolitan) and the Southern region displayed a concerning positive trend after 2009 and 2010, though not statistically significant [APC values of 0.772 (95% CI -0.328 to 4.888), 0.986 (95% CI –0.252 to 4.887), and 0.286 (95% CI –0.061 to 0.772), respectively].ConclusionThese findings underscore the need for targeted interventions with consideration of regional and racial temporal disparities in cervical cancer-related mortality.